COURTSHIP AND MATING BEHAVIOUR OF LIPOLEXIS SCUTELLARIS MACK. (HYMENOPTERA : BRACONIDAE), A PARASITOID OF APHIS GOSSYPII GLOV. (HOMOPTERA : APHIDIDAE) - PANDEY, SHARMLA; SINGH, RAJENDRA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
We report on the courtship and mating behaviour of Lipolexis scutellaris Mack, a parasitoid of Aphis gosypii Glov. The courtship and copulatory behaviour involves the exchange of several sexual stimuli between the two sexes. The actual copulation lasts for 5.6 t 1.36 sec. Mating sequence of the male consisted of wing vibration, approach to the female, visual recognition of the female, antennal contact of female wings, mounting and copulation. Male readily mated more than one female. A fully fed male of L. scutellaris mates. with upto 15 females while starved male mates only with upto 3-4 females in his life. The wasp also exhibit post-copulatory behaviour. Olfaction of pheromones secreted by female plays a significant role in exciting and luring the male. Older mates do not actively court or copulate.